Quantification of Productivity Changes Due to Work Schedule Changes in Construction Projects. A Case Study - E. Arriagada, Ricardo; F. Ararcón C., Luis (Revista de la Construcción. Journal of Construction, 2014)
In a copper-molybdenum open pit mine in Chile, a collective labor dispute in April 2012 halted work on the site; the main problem was the negotiation of unified work schedules for contractors, subcontractors and their own staff. To avoid conflicts that could delay this project, the parties agreed to submit to arbitration by an external agency, to determine and quantify the existence of lost productivity caused by the change of work schedules. The external agency considered three basic elements: a) the temporal dimension to allow the comparison of two work schedules, b) the acceptable range of productivity losses associated with these schedules; and c) an unbiased mechanism to allocate a productivity loss within the range associated with each schedule. This paper presents the analysis of productivity loss when work schedules are extended, the method utilized, and the results obtained. This probabilistic model randomly assigns discrete values of productivity loss for each day of the work schedules, and uses inefficiency ranges from industry research; this allows a non-biased, easy to implement, comparison of work schedules.